Western Cooperage Co. float in Golden Potlatch parade, Seattle, July 1911 - Nowell & Rognon
Seattle’s first Golden Potlatch festival opened on July 17, 1911. The city-wide summer celebration was conceived by civic groups to celebrate the Klondike gold rush and capitalize on the success of the Alaska-Yukon-Pacific Exposition of 1909. The week-long festival included concerts, parades, aircraft and boat demonstrations. Seattle’s annual Seafair celebrations each July continue the Potlatch tradition. This photograph shows Western Cooperage Company's float of a huge wooden barrel on the back of an automobile. The float passes in front of spectators viewing the parade on Third Avenue in Belltown with a grandstand visible in the background. Embossed on front of print: Nowell & Rognan, Seattle. Caption information source: HistoryLink.org. 1 photographic print: b&w; 6 3/4 x 4 7/8 in.